2018
DOI: 10.1038/s41401-018-0074-y
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of cannabinoid ligand-induced modulations in intracellular Ca2+ signals of mouse pancreatic acinar cells in vitro

Abstract: We recently reported that a CBR agonist, GW405833 (GW), reduced both the ACh-induced Ca oscillations and the L-arginine-induced Ca signal enhancement in mouse pancreatic acinar cells, suggesting that GW-induced inhibition may prevent the pathogenesis of acute pancreatitis. In this study, we aim to evaluate the effects of other cannabinoid ligands on Ca signaling in acinar cells. Patch-clamp whole-cell recordings were applied to measure ACh-induced intracellular Ca oscillations in pancreatic acinar cells acutel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Suppression of JNK and stimulation of p38 as well as the MK2signaling pathways may be responsible for mediating the beneficial effects of CB2R stimulation during acute pancreatitis. Moreover, Xia et al (2019) showed that JWH133 prevented acetylcholine-induced Ca 2+ oscillations in mouse pancreatic acinar cells, whereas CB2R-knockout or AM630 blocked the suppressive effects of JWH133. Thus, CB2R activation might play a novel role in modulating the physiology and pathophysiology of pancreatic acinar cells.…”
Section: Pancreatitismentioning
confidence: 99%
“…Suppression of JNK and stimulation of p38 as well as the MK2signaling pathways may be responsible for mediating the beneficial effects of CB2R stimulation during acute pancreatitis. Moreover, Xia et al (2019) showed that JWH133 prevented acetylcholine-induced Ca 2+ oscillations in mouse pancreatic acinar cells, whereas CB2R-knockout or AM630 blocked the suppressive effects of JWH133. Thus, CB2R activation might play a novel role in modulating the physiology and pathophysiology of pancreatic acinar cells.…”
Section: Pancreatitismentioning
confidence: 99%
“…Xia et al intent to answer another important question in cannabinoid research field, the heterogeneity. In the research article "Heterogeneity of cannabinoid ligand-induced modulations in intracellular Ca 2+ signals of mouse pancreatic acinar cells in vitro" authors report a heterogenic effects of cannabinoid ligands on the intracellular Ca 2+ signals in mouse pancreatic acinar cells, demonstrating that cannabinoid ligands exhibit the modulations of intracellular Ca 2+ signals in a heterogenic manner through both cannabinoid receptors and non-receptor mechanisms [9]. In article "Protective effect of cannabinoid receptor 2specific agonist GW405833 on concanavalin A-induced acute liver injury", authors report that CB 2 R agonist GW405833 protects liver cells against acute concanavalin A-induced toxicity through the CB 2 Rs expressed in liver immune cells.…”
mentioning
confidence: 99%
“…Analogously to the findings made in the human pancreas, both CB1R and CB2R have been detected in mouse PACs ( Michalski et al, 2007 ; Linari et al, 2009 ; Huang et al, 2016 ). In vitro studies ( Linari et al, 2009 ; Petrella et al, 2010 ; Cao et al, 2012 ; Huang et al, 2016 ; Xia et al, 2019 ) on CBR in freshly isolated PACs are summarized here ( Supplementary Table 7 ). Of note is that while CBR agonists did not affect basal or carbachol- and cerulein-induced amylase secretion, a non-selective CBR agonist inhibited KCl-elicited elevation in amylase ( Linari et al, 2009 ) as well as reduced cerulein-induced IL-6 and MCP-1 secretion in PACs ( Petrella et al, 2010 ).…”
Section: Endocannabinoid Systemmentioning
confidence: 99%